2012
DOI: 10.1007/s00464-012-2247-y
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic surgeons’ preferences for inguinal hernia repair: TEP, TAPP, or OPEN

Abstract: This survey showed that most surgeons who perform an endoscopic approach for inguinal hernia as the first option are convinced that not all hernias are good indications for this approach. On the other hand, most surgeons think that it is better to be able to offer patients an endoscopic technique or an open approach depending on the case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 32 publications
1
19
0
3
Order By: Relevance
“…Our survey demonstrates that surgeons prefer a tailored approach depending on patient and hernia characteristics, and that a little over half of the surgeons are able to offer a laparoscopic repair depending on the case. A survey by Morales-Conde et al [13] studying preferences for hernia repair in laparoscopic surgeons', similarly found that they use a tailored approach, favoring laparoscopy for recurrent (81 %) and bilateral hernias (93 %).…”
Section: Discussionmentioning
confidence: 88%
“…Our survey demonstrates that surgeons prefer a tailored approach depending on patient and hernia characteristics, and that a little over half of the surgeons are able to offer a laparoscopic repair depending on the case. A survey by Morales-Conde et al [13] studying preferences for hernia repair in laparoscopic surgeons', similarly found that they use a tailored approach, favoring laparoscopy for recurrent (81 %) and bilateral hernias (93 %).…”
Section: Discussionmentioning
confidence: 88%
“…Besides the perishing pathological conditions and possible organ injuries, the extensive adhesiolysis, remnant of hernia sac and the need for mesh fixation with tacks that may be a cause for seroma should also be taken into consideration. Up to now, laparoscopic transabdominal preperitoneal approach (TAPP) is the preferred method to deal with incarcerated hernia by most surgeons [18][19][20][21][22]. Ferzli GS et al [23] have used a combined technique to scrotal hernia.…”
Section: Discussionmentioning
confidence: 98%
“…Ferzli GS et al [23] have used a combined technique to scrotal hernia. Although TEP application is still controversial [18,24,25], lots of researchers are attempting to verify the usage of TEP on complicated and severe hernias [4,16,17,26]. The disposal of hernia sac has attracted enough interests [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…A practice survey of 100 laparoscopic surgeons participating in the 2010 Congress of the European Association of Endoscopic Surgeons revealed that TAPP was the most commonly used technique for laparoscopic inguinal hernia repair. [14] We also used the TAPP technique as we found it technically simpler with better anatomic detail. Additionally, pre-peritoneal balloon dissectors were not routinely available in our setting.…”
Section: Discussionmentioning
confidence: 99%